Simulating of human physiological supersystems: integrative function of organs supporting cell life - Grygoryan, R.D.; Degoda, A.B.; Lyudovyk, T.V.; Yurchak, O.I. (Інститут програмних систем НАН України, 2025)
A quantitative model of fluids’ dynamics (MFD) in the human body is created. Initially, MFD was realized as an autonomous C# software module (SM) functioning under given dynamic input characteristics. Later, SM was incorporated into our special software-modeling tool (SMT) capable of simulating the main modes of the human physiological super-system (PSS) providing cells' life. MFD describes mechanisms regulating long-term blood, lymph, total cells’, and intercellular volumes. SMT simulates both intracellular and multicellular mechanisms providing cell energy balance despite casual dynamics of energy consumption rate. Multicellular mechanisms include complex systems controlling systemic and regional hemodynamics, interaction of the liver with the pancreas, blood filtration in kidneys, bladder function, and liquid expirations in lungs and skin in the background of a dynamic external environment. The latter is a gas atmosphere with altering pressure, illumination, temperature, humidity, and wind speed. Models have been tested using algorithms that design scenarios, including simulation of either short-time or long-time (hours or days) observations. Input data include different combinations of internal and external parameters including osmotic, and oncotic pressures. Output data include the main parameters characterizing organs and life support systems. Both student-medics and physiologists interested in providing theoretical research can be users of SM. Prombles in programming 2024; 4: 77-88